2022
DOI: 10.3390/dj10090159
|View full text |Cite
|
Sign up to set email alerts
|

Risk Characteristics of Peri-Implant Infections: A Retrospective Evaluation in a University Consultation Setting

Abstract: Peri-implantitis is a common biological complication in dentistry. The aim of the present study was to retrospectively analyze risk characteristics in a group of patients referred to a university-based consultation for peri-implantitis. In all, 190 initial cases from 2010 to 2019 were evaluated and descriptively summarized. The evaluation included various parameters such as periodontitis, smoking and oral hygiene status, implant position, type of prosthetic restoration and retention, mucosal quality, and furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…The stability of the outcomes achieved through the present technique is intricately linked to adherence to proper oral hygiene protocols [ 58 ] and the necessity for long-term evaluation [ 59 ]. This endeavor necessitates the guidance and support of dental professionals in assisting patients with their home care routines, taking into careful consideration individual motivation levels and the efficacy of hygiene procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The stability of the outcomes achieved through the present technique is intricately linked to adherence to proper oral hygiene protocols [ 58 ] and the necessity for long-term evaluation [ 59 ]. This endeavor necessitates the guidance and support of dental professionals in assisting patients with their home care routines, taking into careful consideration individual motivation levels and the efficacy of hygiene procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a systematic review underlined that there is a tendency towards more biological complications and even implant failure with cemented restorations when compared with screw‐retained restorations (Sailer et al, 2012). Many studies evaluated cemented implant restorations and identified cement residues within the peri‐implant tissues as reason for peri‐implant inflammations (Linkevicius et al, 2013; Schwartzenberg et al, 2022; Staubli et al, 2017; Wilson Jr, 2009). However, because of the small sample size and lack of power no conclusions can be drawn.…”
Section: Discussionmentioning
confidence: 99%